2010
DOI: 10.1016/j.psep.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterisation of activated sludge behaviour during mechanical expression

Abstract: Even after mechanical dewatering, activated sludge contains a large amount of water. Due to its biological nature, composition and also the type of treatment it comes from, this material is usually highly compressible and known to be difficult to dewater. In the present work various tests are proposed to try to highlight some aspects which could explain the poor dewaterability of activated sludge. Experiments of expression were carried out in a Filtration-Compression Cell for semi-solid samples of sludge. Oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although several researchers have studied the expression characteristics of sludge, the above questions have not been explained in detail. [16][17][18] Novak et al [14] reported the effect of filtration pressure on expression performance when the expression pressure was limited to below 300 kPa, which is much less than that in practice. On the other hand, the filtration and expression apparatus they employed was batch feed and the expressed water may be as little as 2-4 mL, neither of which matches with plant-scale operation.…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers have studied the expression characteristics of sludge, the above questions have not been explained in detail. [16][17][18] Novak et al [14] reported the effect of filtration pressure on expression performance when the expression pressure was limited to below 300 kPa, which is much less than that in practice. On the other hand, the filtration and expression apparatus they employed was batch feed and the expressed water may be as little as 2-4 mL, neither of which matches with plant-scale operation.…”
Section: Introductionmentioning
confidence: 99%